Platinum (IV) Derivatives with Cinnamate Axial Ligands as Potent Agents Against Both Differentiated and Tumorigenic Cancer Stem Rhabdomyosarcoma Cells - Zajac, Juraj; Novohradsky, Vojtech; Markova, Lenka; Brabec, Viktor; Kasparkova, Jana (Angewandte Chemie (International ed. in English), 2020)
To design an anticancer drug capable of inhibiting not only the proliferation of the differentiated tumor cells but also reducing the tumorigenic capability of cancer stem cells (CSCs), the new PtIV prodrugs with axial cinnamate ligands were synthesized. We demonstrate their superior antiproliferative activity in monolayer and 3D spheroid antiproliferative activity tests using panel of cancer cell lines. An outstanding activity was found against rhabdomyosarcoma cells, one of the most problematic and poorly treatable pediatric tumors. The results also suggest that the released PtII compound inhibits antiproliferative activity of cancer cells by DNA-damage mediated mechanism; the released cinnamic acid can trigger processes leading to differentiation, making the CSCs more sensitive to killing by the platinum part of the complex. PtIV complex with axial cinnamate ligands is the first PtIV prodrug capable of overcoming CSCs resistance and induce death in both CSCs and bulk cancer.
Keywords: lidé; cinnamáty; Cinnamates; Neoplastic Stem Cells; Humans; cancer; antitumor agents; buněčná diferenciace; platina; Rhabdomyosarcoma; nádorové kmenové buňky; drug design; rhabdomyosarkom; Models, Molecular; Platinum; molekulární modely; ligandy; Cell Differentiation; platinum; Ligands; cancer stem cells